2016
DOI: 10.1093/mnras/stw871
|View full text |Cite
|
Sign up to set email alerts
|

Identifying IGR J14091−6108 as a magnetic CV with a massive white dwarf using X-ray and optical observations

Abstract: IGR J14091-6108 is a Galactic X-ray source known to have an iron emission line, a hard X-ray spectrum, and an optical counterpart. Here, we report on X-ray observations of the source with XMM-Newton and NuSTAR as well as optical spectroscopy with ESO/VLT and NOAO/SOAR. In the X-rays, this provides data with much better statistical quality than the previous observations, and this is the first report of the optical spectrum. Timing analysis of the XMM data shows a very significant detection of 576.3 ± 0.6 s peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 44 publications
3
26
1
Order By: Relevance
“…In the previous paper (Krivonos et al 2012), we pre- Lutovinov et al 2013b, for details). A number of multi-wavelength follow-up observations were initiated to unveil the nature of these unclassified objects (Karasev et al 2012;Masetti et al 2013;Revnivtsev et al 2013;Zolotukhin & Revnivtsev 2015;Lutovinov et al 2013aLutovinov et al , 2015Tomsick et al 2015Tomsick et al , 2016aClavel et al 2016;Burenin et al 2016;Rahoui et al 2017) which led to the classification of 11 sources (shown by solid red circles in Fig. 1), rising the total survey identification completeness from ∼92% to ∼94%.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous paper (Krivonos et al 2012), we pre- Lutovinov et al 2013b, for details). A number of multi-wavelength follow-up observations were initiated to unveil the nature of these unclassified objects (Karasev et al 2012;Masetti et al 2013;Revnivtsev et al 2013;Zolotukhin & Revnivtsev 2015;Lutovinov et al 2013aLutovinov et al , 2015Tomsick et al 2015Tomsick et al , 2016aClavel et al 2016;Burenin et al 2016;Rahoui et al 2017) which led to the classification of 11 sources (shown by solid red circles in Fig. 1), rising the total survey identification completeness from ∼92% to ∼94%.…”
Section: Introductionmentioning
confidence: 99%
“…The measured parallax has a large relative uncertainty (∼ 40%), J17528's X-ray spectrum is well described by a partially covered thermal bremsstrahlung model with a narrow neutral Fe line and a possible reflection component. This type of spectrum is most typically observed in CVs (e.g., Mukai et al 2015;Tomsick et al 2016). Furthermore, the source's optical spectrum shows a strong Hα emission line as well as weak He I lines, likely being produced by an accretion column or disk.…”
Section: Igr J20063+3641mentioning
confidence: 84%
“…For both sources, we found that, if the reflection amplitude is left free, the fit prefers values > 1.0. However, this value is unphysical under the condition that we see all of the direct emission (see e.g., Tomsick et al 2016). Therefore, we fix this parameter to a value of 1 in the fits for both sources.…”
Section: Reflection Fitsmentioning
confidence: 99%
“…With the aim of better understanding the population of faint HMXBs, our initial target selection was the sample of twenty-six sources listed as unidentified by Lutovinov et al (2013, see Table 1). As of today, six of these sources have been observed by NuSTAR five through our Legacy program (see Table 2) and one through an independent program (Tomsick et al 2016b). Using the results provided by these six observations, we first discuss how NuSTAR can be efficiently used to investigate the population of faint hard X-ray sources in Section 4.1.…”
Section: Discussionmentioning
confidence: 99%
“…3.2.1). In addition, variability studies performed on the NuSTAR light curves were powerful tools to describe the properties of faint IGR sources, especially the detection of eclipses in IGR J18293-1213 (Clavel et al 2016) and the confirmation of both a pulsation period and a decrease of the pulse fraction with energy in IGR J14091-6108 (Tomsick et al 2016b). Therefore, combined with observations at other wavelengths, NuSTAR can be efficiently used to classify faint hard X-ray sources towards the Galactic plane and to better constrain their individual characteristics.…”
Section: Source Classification Using Nustarmentioning
confidence: 99%